Recreation of Fantastic Elements in the Translation of the Fairy Tale Novel about "Dunno" - D. Ch. Igamuratova (International Journal on Integrated Education, 2022)
The article analyzes the Uzbek translation of fantastic elements in fairy tale novels dedicated to "Dunno" and his friends, as well as the embodiment of the author's fantasy in the modern era.